How institutional and interpersonal variables impact international L2 students' language gains at university. (August 2018) - Deygers, Bart
Abstract: As higher education has grown into a global enterprise, international students have become an integral part of the student population at many universities. Given this reality, it is striking that there are considerable gaps in our knowledge of whether and why international students make language gains, or fail to do so. In order to address these voids in research, this study employed a longitudinal mixed-methods design to measure oral and written gains made by international L2-Dutch students studying in universities in Flanders over an eight-month period. It also sheds light on the institutional and social contexts of the participants, as measured by longitudinal in-depth interviews. The quantitative data indicate that the participants made no demonstrable gains except on one sole indicator of written fluency, and the qualitative findings reveal that linguistic readiness, perceived linguistic inferiority, and a lack of access to the L1 community hampered students' opportunities and willingness to engage in meaningful interaction. This study offers no immediate reason to presume that rich input alone yields language gains, even with advanced learners in an academic context. Rather, it reaffirms the hypothesis that language learning in a naturalistic setting is driven by meaningful interaction and a sense of belonging.